Sustainable corporate environmental information disclosure: Evidence for green recovery from polluting firms of China - Long, Fengjiao; Chen, Qin; Xu, Lu; Wang, Jian; Vasa, László (Frontiers in Environmental Science, 2022)
For a greener society, good corporate environmental information disclosure is crucial. This study empirically examines the influence of media attention and state-owned equity, and their interaction on corporate environmental information disclosures by A-share heavily polluting firms in Shanghai and Shenzhen stock markets from 2015 to 2020. The results show that state-owned equity can improve the level of corporate environmental information disclosure; however, it mainly affects financial environmental information disclosure. Media attention also improves the level of corporate environmental information disclosure, but only for non-financial environmental information. Moreover, media attention and state-owned equity have a certain substitution effect on environmental information disclosure; a higher state-owned equity ratio weakens the positive effect of media attention on environmental information disclosure. The study discussed the implications and novel conclusions for green image, greener recovery and sustainable development perspectives. The findings can be useful for further promoting corporate environmental information disclosure and developing relevant policies.